A antropologia filosófica de Henrique Cláudio de Lima Vaz como inspiração para um modelo de educação - Andrade, Paulo Raphael Oliveira (2023)
The purpose of this doctoral thesis is to develop a reflection on Philosophical Anthropology as a model of education inspiration, proceeding from a dialogue with the work of Henrique Cláudio de Lima Vaz, specifically Philosophical Anthropology. It takes as its starting point the relationship between anthropology and education, seeking to address the educational themes that are transversely present in Lima Vaz’s work. Based on a comprehensive view of the human being, we analyzed modern educational problems, conducting a historical aporia of education in Brazil. From this analysis, it was observed that education is oriented towards the demands of the financial system and the labor market, which require students to develop certain skills useful for the working world, but not a deep understanding of the universe in which they live, in order to become fully realized individuals. It is argued that Lima Vaz provided a profound diagnosis of the modern problem and pointed towards a good solution, namely: an education with anthropological, ethical, and metaphysical foundations, beyond equipping students for useful roles from the perspective of science and technology, opens up the possibility of leading a fulfilled and meaningful life, and acting virtuously within the ethical community. To evaluate the philosophical scope of Lima Vaz’s solution to the educational issue, the category of realization and person as educational models were clarified. The final category is anthropological discourse, which is of the person, founded on the analogy of being, based on the Thomistic metaphysical conception of esse, where being a person is expressiveness, transition from given to meaning. In conclusion, it is succinctly highlighted that the purpose of education is to become what one is, namely, a person